Advertising literacy among low-income community in the context of fly postings in Malaysia’s reality digital environment / Neesa Ameera Mohammed Salim … [et al.] - Mohammed Salim, Neesa Ameera; Shahizan Ali, Mohd Nor; Shawalludin, Syahrini; Mohd Khalis, Faryna (Universiti Teknologi MARA, Kedah, 2020)
Digital inclusion is the ability of an individual or a group to access and acquire information in the context of communication technologies. The digital age today permeates the society through vehicles of information including advertising. The society are able to access any sorts of advertising messages even from the palm of their hands. However, the issue is no longer in the context of accessing the information, but the literacy skills, or specifically the advertising literacy skills in carefully selecting valid and reliable information with the focus on the aspect of security in today’s digital environment. This study aims to identify the advertising literacy and how the digital inclusion impinges the low- income community in the context of fly posting in Malaysia. This is a quantitative study which used survey as a research design by distributing questionnaires to a total of 574 respondents from five selected Public Housing Program (PHP) in Klang Valley, Kuala Lumpur which have been selected based on the random stratified sampling to represent the low income distribution. Findings revealed that the low-incomes’ advertising literacy level is high due to digital inclusion factor. This study reveals how digital and media research in the advertising landscape affects the literacy level of the low-income community as the discussion provided in this study adds on to the discussion of the current advertising research.